A method for linkage analysis - Temel, Tugrul (International Service for National Agricultural Research, 2002)
This paper introduces a simple method to characterize linkages among organizations in a system. Data required are collected by a questionnaire with scaled answers. This method can be applied to determine dominant and subordinate organizations, identify weak linkages among them, and give insights into linkage mechanisms to be established. Having accomplished these, decision makers will be in a position to design formal rules and procedures that facilitate the growth of desired linkages.